Buerger Allen Exercise In Type 2 Diabetes Mellitus Patients: A Literature Review - Sari, Mutmainnah; Jamaluddin, Ahmad; Hafid, Muhammad Anwar; Risnah, Risnah (Universitas Muhammadiyah Semarang, 2024)
An effort that might be made to prevent complications of Diabetes Mellitus (DM) is by increasing peripheral blood circulation through the Buerger Allen exercise (BAE). Previous studies recommend reviewing the standard procedure of the BAE. Research related to the review of the effectiveness of BAE application on type 2 DM, which is summarized from various studies in latest original research is still lacking. The aim of this study is to describe the standard form of the Buerger Allen implementation that has been evaluated its effectiveness in patients with type 2 DM patients with complications. This literature review was performed with PICO keywords in 4 databases, including PubMed, Springer Link, Wiley Online Library, and Google Scholar in 2011-2022. We have concluded that the standard procedure for implementing the BAE consists of 5 stages and three main steps for each cycle. The steps are supine position (pre-exercise), elevation, Hanging, flexion-extension, and horizontal (post-exercise) steps. Each session consists of at least 3 to 6 cycles with approximately 30 minutes. Fifteen articles analyzed showed significant changes in lower peripheral perfusion of patients with type 2 DM. BAE is a simple non-pharmacological intervention that is considered an effective method for managing lower peripheral perfusion.